In silico and in vitro evaluation of tetrahydropyridine compounds as efflux inhibitors in Mycobacterium abscessus. (September 2019) - Ramis, Ivy B.; Vianna, Júlia S.; Silva Junior, Lande; von Groll, Andrea; Ramos, Daniela F.; Lobo, Marcio Marçal; Zanatta, Nilo; Viveiros, Miguel; Silva, Pedro E. Almeida da
Abstract: Herein, we evaluated tetrahydropyridine (THP) compounds (NUNM) as antimicrobials and inhibitors of the efflux mechanism in M. abscessus . subsp. abscessus . The modulation factor (MF) of efflux inhibitors was calculated from the minimum inhibitory concentrations (MICs) of amikacin (AMI), ciprofloxacin (CIP) and clarithromycin (CLA) in the absence and presence of subinhibitory concentrations of the NUNM compounds and canonical inhibitors carbonyl cyanide m -chlorophenyl hydrazone (CCCP) and verapamil (VP). The kinetics of the intracellular accumulation of the fluorimetric substrate ethidium bromide (EtBr) was evaluated and calculated by the relative final fluorescence (RFF). In addition, molecular modeling simulations for the MmpL5 and Tap efflux transporters with ligands (CLA, NUNM, CCCP, VP and EtBr) were performed to better understand the efflux mechanism. We highlight the NUNM01 compound because it reduced the MICs of AMI, CIP and CLA by 4-, 4- and 16-fold, respectively, had the highest effect on EtBr accumulation (RFF = 3.1) and showed a significant in silico affinity for the evaluated proteins in docking simulations. Based on the analyses performed in vitro and in silico, we propose that NUNM01 is a potential pharmacophore candidate for the development of a therapeutic adjuvant for M. abscessus infections.